1984
DOI: 10.1159/000183288
|View full text |Cite
|
Sign up to set email alerts
|

Multicystic Transformation of Kidneys in Chronic Renal Failure

Abstract: With real-time sonography, 120 nondialyzed uremic patients prior to hemodialysis, 108 patients on maintenance hemodialysis and 9 patients postdialysis after successful homotransplantation were examined for the presence of renal cysts. Even in incipient renal failure, multiple cysts were demonstrable in some patients (at a serum creatinine of 3 mg/dl in 22% of patients), particularly in patients with analgesic nephropathy. When hemodialysis was started (serum creatinine approximately 10 mg/dl), 35% of the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
1
5

Year Published

1988
1988
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 18 publications
0
38
1
5
Order By: Relevance
“…In 1980, Bommer et al [5]reported that acquired renal cysts were observed by CT scan in patients with predialysis end-stage renal disease. In other words, acquired cysts develop in patients with serum creatinine >2 mg/dl [7]. The most important factor for developing acquired cyst is the duration of chronic renal failure or dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…In 1980, Bommer et al [5]reported that acquired renal cysts were observed by CT scan in patients with predialysis end-stage renal disease. In other words, acquired cysts develop in patients with serum creatinine >2 mg/dl [7]. The most important factor for developing acquired cyst is the duration of chronic renal failure or dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…El tumor renal en el paciente trasplantado aparece en edades más jóvenes que en la población general con una edad media de aparición entre 44 y 47 años; siendo la proporción hombre mujer de 2 a 17,10 . La ERQA fue descrita por primera vez en 1977 por Dunnill et al, definiéndose como la sustitución de mas del 25% del parénquima renal en pacientes con IRC por quistes córtico-medulares que se desarrollarían durante la diálisis, aunque se han descrito en pacientes con IRC prediálisis 15,18 . Etiopatogéni-camente se han propuesto distintos mecanismos en la ERQA: obstrucción por depósitos de oxalato o fibrosis, productos tóxicos acumulados que alterarían la membrana basal, alteraciones vasculares secundarias a la hemodiálisis, factores renotrópicos de crecimiento 17 .…”
Section: Discussionunclassified
“…Histológicamente se caracteriza por la presencia de quistes, cubiertos de epitelio cuboidal, columnar, o hiperplásico con proyecciones papilares. estudios patológicos han demostrada la continuidad de estos quistes con los túbulos renales, sugiriéndose el origen quístico en los túbulos, sin poder determinar si el origen es del túbulo proximal o distal 8,9,15 . Así los quistes tapizados por epitelio cuboidal se estratificaría, con posterior hiperplasia y displasia que daría lugar al tumor 18 .…”
Section: Discussionunclassified
See 2 more Smart Citations